PENGARUH METODE PEMBELAJARAN SOSIODRAMA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SEJARAH - Badarudin, Badarudin; Tohri, Ahmad; Asror, M Zainul (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2022)
This research aims to determine the differences in learning outcomes of students in the History Education Study Program at Hamzanwadi University who are taught through the sociodrama method and the lecture method. This research uses a quasi-experimental method. The research design used a 2x2 by level treatment design. The sampling technique uses multistage random sampling. The total sample was 44 students who were divided into 22 experimental groups and 22 control groups. Data collection uses two methods, namely tests and questionnaires. Data analysis used descriptive and inferential techniques, two-way ANOVA. The results of analysis of research data with a significance level of α 0.05 showed that Fcount (Fh = 7.77) was greater than Ftable (Ft α 0.05 = 4.08). This is in accordance with the average value of history learning outcomes for the group of students taught using the sociodrama method ȲA1 = 26.68 and the group of students taught using the lecture method ȲA2 = 23.23;. The results of this data analysis show that the history learning outcomes of the student group taught using the sociodrama method were higher than the learning outcomes of the student group taught using the lecture method